A governança como determinante de desenvolvimento: um estudo de caso na cadeia produtiva de frutas no norte do Espírito Santo - Braga, Ayala Liberato (2010)
In the last few years, particularly in the beginning of the century, there has been seen a strong movement to deliver innovative alternatives to economic development, to consider issues relating to poverty and income generation. The study of fruit production chain in northern of Espírito Santo state seeks to understand the forms of interaction among economic agents, social and political as well as external forces that interfere with the process of production, processing and marketing of juices and pulps fruit, proposing a conceptual model of management, involving all economic agents and has a focus on small farmers. This work is characterized as exploratory, and its methods of data collection, document analysis, semistructured interviews and observation. First, we tried to identify how the cooperatives organize their supply chain. Subsequently, we sought to understand why the fruit has different forms of governance in its production chain. And finally, we analyzed the main characteristics of each of these coordination mechanisms analyzed. Semi-structured interviews with representative members of cooperatives: COOPRUJ (Cooperative of Jaguaré Rural Producers) and COOPCRISTAL (Producers Cooperative Cane Crystal), Family Farmers Cooperative of Colatina (CAF) and agribusinesses Trop Brazil and Sucos Mais . These cooperatives were selected because they are more structured in the marketing process. To perform the analysis of the interviews was chosen the content analysis. Both in COOPCROSTAL, as in COOPRUJ as the CAF, was verified the following structure: with respect to behavioral assumptions, were detected low levels of opportunism, especially the pre-contractual opportunism on the trading price and pruning of fruit (which determines harvest). With respect to the attributes of the transaction, is often recurrent, with emphasis on asset specificity (locational, physical, temporal and dedicated specificity). Regarding to the governance structure, there is the hybrid, with long-term business relationships and with neoclassical contracts.